Can opioid vigilance and patient-centered care coexist? A qualitative study of communicative tensions encountered by surgical trainees - Adams, MA, Elizabeth Troutman; Cohen, PhD, Elisia L.; Bernard, MD, Andrew; Darnell, PhD, Whittney H.; Oyler, PharmD, Douglas R. (Journal of Opioid Management, 2020)
Objective: The American health care system’s adoption of the patient-centered care (PCC) model has transformed how medical providers communicate with patients about prescription pain medication. Concomitantly, the nation’s opioid epidemic has necessitated a proactive response from the medical profession, requiring providers who frequently dispense opioids for acute pain to exercise vigilance in monitoring and limiting outpatient prescriptions. This qualitative study explores how surgical trainees balance PCC directives, including shared decision making, exchanging information with patients, and relationship maintenance, with opioid prescribing vigilance. Design: Investigators conducted interviews with 17 surgical residents and fellows (trainees) who routinely prescribe opioids at an academic medical center. Results: A qualitative descriptive analysis produced four codes, which were reduced to themes depicting problematic intersections between PCC imperatives and opioid vigilance during post-operative opioid-prescribing communication: (a) sharing the decision-making process contended with exerting medical authority, (b) reciprocating information contended with negotiating opioid prescribing terms with patients, (c) maintaining symbiotic relationships contended with prescribing ethics, and (d) achieving patient satisfaction contended with safeguarding opioid medications. Conclusion: Surgical training programs must supply trainees with post-surgical prescribing guidelines and communication skills training. Training should emphasize how PCC directives may work in tandem with–not in opposition to–opioid vigilance.